Solve this problem by using Hilbert style proof:

$ A,B \vdash A \equiv B $

my try :

  • (1) A (hyp)
  • (2) B (hyp)
  • (3) $ A \land B $ (merge)
  • (4) $ A \land B \equiv A \equiv B \equiv A \lor B $ (golden rule)
  • (5) $ A \equiv B \equiv A \lor B $ (3,4 + equ)
  • (6) $ A \lor B \equiv A \equiv B $ (Symmetry)

That was my try. I don't know if it was right. I couldn't continue.

Inference rules : leibniz and equanimity.

Lists of axioms and theorems :

enter image description here

enter image description here

enter image description here

  • $\begingroup$ What are the axioms and/or rules of inference of your system? $\endgroup$ – Doug Spoonwood Feb 3 '14 at 4:51
  • $\begingroup$ @DougSpoonwood Please see my edit for the axioms and rules of inference. $\endgroup$ – Out Of Bounds Feb 3 '14 at 5:04

We will start from George Tourlakis, Mathematical Logic (2008), Example 2.5.1(1), page 77 :

(1) $\quad A, B \vdash A \land B$

and use the Golden Rule, page 43 :

$$(A \land B) \equiv (A \equiv (B \equiv A \lor B))$$

Applying Equanimity [page 40], from (1) we have :

(2) $\quad A,B \vdash (A \equiv (B \equiv A \lor B))$

From the axiom about Associativity of $\equiv$ : $(A \equiv (B \equiv C)) \equiv (A \equiv B) \equiv C)$, by Equanimity :

(3) $\quad A,B \vdash (A \equiv B) \equiv (A \lor B)$

Using again Example 2.5.1(3) :

(4) $\quad A \vdash A \lor B$

we apply again Equanimity :

(5) $\quad A,B \vdash (A \equiv B)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.